Presidential Powers, Immunities, and Pardons - Alberto R. Gonzales (Washington University Law Review, 2019)
Special Counsel Robert Mueller is conducting an investigation into Russia’s interference in the 2016 presidential election and the possible coordination and cooperation with the Donald Trump presidential campaign. The investigation has raised numerous legal questions with serious political and legal implications. Chief among them is whether a sitting President can be indicted and prosecuted for criminal wrongdoing. A related question is whether and to what extent, in the event of an official investigation, a sitting President can be compelled to provide evidence—in the form of oral and written testimony, as well as documentary evidence. Finally, assuming there is potential criminal liability, does a sitting President have the power to issue a self-pardon? These are relatively novel questions in the law, and it is not surprising there is little guidance from the courts given the reluctance by most judges to weigh in on potentially serious political questions. This Article intends to clarify some of the more difficult legal issues in our nation’s separation of powers jurisprudence. In order to afford the President the flexibility and discretion necessary to discharge presidential duties, the courts are almost certainly going to recognize total immunity from the criminal process for the President with respect to official conduct. The treatment of unofficial conduct is less predictable. Based on precedent and our nation’s founding principles of equal justice and fairness, the courts are likely to hold that a sitting President is not above the law and thus does not enjoy immunity from criminal prosecution for unofficial acts or conduct unrelated to his or her fitness to hold office. However, because of separation of powers considerations, the courts are likely to require deferral of any such prosecution until the President no longer holds office. Although not as clear, constitutional considerations would likely also require deferral of any investigation or indictment, at least those requiring the direct and material participation of the President. On the other hand, the President can be compelled to produce certain documentary evidence when doing so is necessary and would otherwise be unavailable in connection with a criminal investigation. The argument for presidential immunity with respect to production of evidence is stronger, though likely not absolute, with respect to oral testimony. Nonetheless, mindful of the President’s duties, the courts are likely to afford the President great latitude in the time, place, and manner of providing oral testimony. Finally, there is nothing in the Constitution that expressly prohibits or limits the President from issuing a self-pardon.
Keywords: Presidential pardons; Presidential immunity; Separation of powers; Constitutional law; Special counsel; Russia investigation; Executive power; Executive privilege